Personal and Organizational Responsibility in the Delivery of Healthcare Services: Breaking the Code of Silence - George Miaoulis; Ivan M. Manev (Health Services Insights, 2025)
Background: This exploratory study investigates the code of silence in healthcare, exploring its origins and outlining its negative impact on healthcare quality and patient safety. Drawing parallels with other professions where similar codes exist, the research delves into the reasons healthcare professionals may choose not to report inappropriate practices. Objective: This article outlines the reasons for the existence of the code of silence in healthcare, assesses its prevalence, and suggests strategies to address it. Design and methods: This is a qualitative study which uses in-depth interviews with 88 licensed healthcare providers (physicians, nurses, administrators, and pharmacists) to identify common types of inappropriate practices, the actions taken to address them, and the reasons why observers chose to remain silent. Results: We find that the majority of healthcare providers in the sample (nearly 70%) either witnessed or were made aware of incidents of inappropriate practices. In a substantial proportion (about 40%) of the cases, no action was taken after reporting the inappropriate practice. The findings are discussed in the context of existing codes of professional ethics and the organizational cultures that either encourage or discourage transparency. The study highlights the tension healthcare professionals face between their personal values, institutional goals, and fear of retribution. Conclusion: Breaking the code of silence is both a personal and organizational responsibility. The paper concludes with actionable recommendations to break the code of silence, such as fostering a supportive reporting culture, improving anonymous reporting mechanisms, and encouraging leadership to prioritize accountability.